2008
DOI: 10.1007/s10620-008-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

Acidic and Basic Solutions Dissolve Protein Plugs Made of Lithostathine Complicating Choledochal Cyst/Pancreaticobiliary Maljunction

Abstract: Protein plugs in choledochal cysts are dissolved in acidic and basic solutions, which may eliminate longitudinal electrostatic interactions of the lithostathine protofibrils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Insoluble lithostathine forms raw fibers through self‐assembly by means of electrical coupling, which are gathered together to create protein plugs . Experimentally, electric coupling is eliminated by acid and base, and protein plugs are dissolved .…”
Section: Chapter Iv: Treatments and Diagnosismentioning
confidence: 99%
“…Insoluble lithostathine forms raw fibers through self‐assembly by means of electrical coupling, which are gathered together to create protein plugs . Experimentally, electric coupling is eliminated by acid and base, and protein plugs are dissolved .…”
Section: Chapter Iv: Treatments and Diagnosismentioning
confidence: 99%
“…Many authors reported protein plugs and/or stones in the common channel in children with congenital fusiform biliary dilatation, which resulted in common biliary obstruction and caused clinical symptoms. [ 14 15 ] The abdominal pain is a main symptom of our 18 patients. Of the patients, elevated serum and urinary amylase occured in 13 patients when abdominal pain appeared.…”
Section: Discussionmentioning
confidence: 99%